QARAQALPAQSTAN RESPUBLIKASÍN TURAQLÍ RAWAJLANDÍRÍW FAKTORÍ SÍPATÍNDA SOCIAL-EKONOMIKALÍQ SIYASAT BASQÍShLARÍNÍŃ ASPEKTLERI - Djumageldiev, N.R. (SCIENCE and SOCIETY, 2025)
The article examines the issues of research of historical stages of development of the conducted analysis on the issues of development of stages of socio-economic policy of Karakalpakstan. The solution of issues of national strategy, programs and action plans in the field of environmental protection provides the basis for the development of innovative approaches to the policy of sustainable development of the Republic of Karakalpakstan.